Evaluación técnico-financiera de la implementación de brocas híbridas para la perforación de la sección superficial 12 ¼” en un campo petrolero (2019)
The main objective of this project is to evaluate technically and financially the implementation of hybrid drills bit in the drilling of section 12 ¼ "of 2 vertical wells of the Field X. In the first drilling was analyzed according to parameters such as: revolutions per minute RPM, WOB, the torque, the specific mechanical energy MSE, the flow, the SPP pressure and the lithology of the lithostratigraphic unit, the performance, the wear of the drill bit and the operation times, the second part was carried out using the indicator Present Net value methodology (VPN). The project was structured in six (6) chapters; Beginning with the aspects associated with the generalities and geology of the field in the Llanos Basin. Subsequently, a theoretical-conceptual framework focused on the types of drilling and drilling; consequently, with the aspects inherent to the implementation of the drills used in the wells and the operational and hydraulic parameters under which the operations were performed and their performance through the drilling of the Formation. Finally, a financial analysis of the implementation of the simulation of kymera in wells D and E was carried out, to integrate it in the technical information and determine the best option in terms of costs and operating parameters. The above, to observe the performance of the tool and understand its performance, looking for applicability in other nearby areas of the Llanos Basin.